Teacher collaboration: Significant influence on self-efficacy of secondary school teachers - Nor Syahrul Bariyah Johari; Norazlinda Saad; Marini Kasim (Institute of Advanced Engineering and Science, 2022)
Teacher collaboration is an aspect that needs to be given due attention in the educational institutions in order to sustain the improvement of teachers’ learning. This study was conducted to examine the influence of secondary school teacher’s collaboration on their self-efficacy. Research design was based on quantitative approach by cross-sectional survey. Data collection via questionnaires was performed to obtain demographic information of respondents, as well as data on teacher collaboration and self-efficacy. A number of 410 secondary school teachers in the northern part of peninsular Malaysia were involved in the study as survey respondents. The collected data was processed and analyzed using statistical package for the social sciences (SPSS) via frequency, mean, standard deviation, Pearson correlation and multiple regression analysis. The study found that the level of teacher collaboration and teachers’ self-efficacy among secondary school teachers is high. The findings also discovered that there was positive relationship between teacher collaboration and teachers’ self-efficacy. In addition, the dimension of teacher collaboration was found to have a significant influence on the teachers’ self-efficacy. Thus, the findings clearly indicated the importance of the collaboration practices between teachers in influencing the self-efficacy of teachers.